Axicabtagene ciloleucel in relapsed or refractory indolent non-Hodgkin lymphoma (ZUMA-5): a single-arm, multicentre, phase 2 trial. Issue 1 (January 2022) - Jacobson, Caron A; Chavez, Julio C; Sehgal, Alison R; William, Basem M; Munoz, Javier; Salles, Gilles; Munshi, Pashna N; Casulo, Carla; Maloney, David G; de Vos, Sven; Reshef, Ran; Leslie, Lori A; et al.
Summary: Background: Most patients with advanced-stage indolent non-Hodgkin lymphoma have multiple relapses. We assessed axicabtagene ciloleucel autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy in relapsed or refractory indolent non-Hodgkin lymphoma. Methods: ZUMA-5 is a single-arm, multicentre, phase 2 trial being conducted at 15 medical cancer centres in the USA and two medical cancer centres in France. Patients were eligible if they were aged 18 years or older, with histologically confirmed indolent non-Hodgkin lymphoma (follicular lymphoma or marginal zone lymphoma), had relapsed or refractory disease, previously had two or more lines of therapy (including an anti-CD20 monoclonal antibody with an alkylating agent), and an Eastern Cooperative Oncology Group performance score of 0 or 1. Patients underwent leukapheresis and received conditioning chemotherapy (cyclophosphamide at 500 mg/m 2 per day and fludarabine at 30 mg/m 2 per day on days −5, −4, and −3) followed by a single infusion of axicabtagene ciloleucel (2 × 10 6 CAR T cells per kg) on day 0. The primary endpoint was overall response rate (complete response and partial response) assessed by an independent review committee per Lugano classification. The primary activity analysis was done after at least 80 treated patients with follicular lymphoma had been followed up for at least 12 months after the first response assessment at week 4 after infusion. The primary analyses were done in the per-protocol population (ie, eligible patients with follicular lymphoma who had 12 months of follow-up after the first response assessment and eligible patients with marginal zone lymphoma who had at least 4 weeks of follow-up after infusion of axicabtagene ciloleucel). Safety analyses were done in patients who received an infusion of axicabtagene ciloleucel. This study is registered with ClinicalTrials.gov, NCT03105336, and is closed to accrual. Findings: Between June 20, 2017, and July 16, 2020, 153 patients were enrolled and underwent leukapheresis, and axicabtagene ciloleucel was successfully manufactured for all enrolled patients. As of data cutoff (Sept 14, 2020), 148 patients had received an infusion of axicabtagene ciloleucel (124 [84%] who had follicular lymphoma and 24 [16%] who had marginal zone lymphoma). The median follow-up for the primary analysis was 17·5 months (IQR 14·1–22·6). Among patients who were eligible for the primary analysis (n=104, of whom 84 had follicular lymphoma and 20 had marginal zone lymphoma), 96 (92%; 95% CI 85–97) had an overall response and 77 (74%) had a complete response. The most common grade 3 or worse adverse events were cytopenias (104 [70%] of 148 patients) and infections (26 [18%]). Grade 3 or worse cytokine release syndrome occurred in ten (7%) patients and grade 3 or 4 neurological events occurred in 28 (19%) patients. Serious adverse events (any grade) occurred in 74 (50%) patients. Deaths due to adverse events occurred in four (3%) patients, one of which was deemed to be treatment-related (multisystem organ failure). Interpretation: Axicabtagene ciloleucel showed high rates of durable responses and had a manageable safety profile in patients with relapsed or refractory indolent non-Hodgkin lymphoma. Funding: Kite, a Gilead Company